Private placements of seasoned equity issues : shareholders' wealth, firm performance, and stock liquidity. - Ho, Kim Wai. (2011)
Seasoned public equity offerings have been extensively researched in the United States and elsewhere. In contrast, the literature on private placements of seasoned equity issues is rather limited. Existing studies on private equity sales use data from the U.S. and Japanese markets and focus mainly on short-term wealth effects. Results of these studies may reflect the regulatory and issuing characteristics in those markets. This dissertation extends the literature by examining the private placements of seasoned equity issues in Singapore. Unlike those in the U.S. and Japan, private equity sales in Singapore are restricted in terms of issue size and the degree of price discount. In addition, new shares cannot be placed out to directors and substantial shareholders. Because of these restrictions, private placements of seasoned equity issues in Singapore are associated with important ownership structure changes. The central theme of the dissertation is to examine the impact of these ownership structure changes on the valuation, both short- and long-term, and financial consequences of this form of financial structure rearrangement.